New Medical Device Acquisition During Pediatric Severe Sepsis Hospitalizations. Issue 5 (May 2020) - Carlton, Erin F.; Donnelly, John P.; Hensley, Matthew K.; Cornell, Timothy T.; Prescott, Hallie C.
Abstract : Objectives: Severe sepsis is a significant cause of healthcare utilization and morbidity among pediatric patients. However, little is known about how commonly survivors acquire new medical devices during pediatric severe sepsis hospitalization. We sought to determine the rate of new device acquisition (specifically, tracheostomy placement, gastrostomy tube placement, vascular access devices, ostomy procedures, and amputation) among children surviving hospitalizations with severe sepsis. For contextualization, we compare this to rates of new device acquisition among three comparison cohorts: 1) survivors of all-cause pediatric hospitalizations; 2) matched survivors of nonsepsis infection hospitalizations; and 3) matched survivors of all-cause nonsepsis hospitalization with similar organ dysfunction. Design: Observational cohort study. Setting: Nationwide Readmission Database (2016), including all-payer hospitalizations from 27 states. Patients: Eighteen-thousand two-hundred ten pediatric severe sepsis hospitalizations; 532, 738 all-cause pediatric hospitalizations; 16, 173 age- and sex-matched nonsepsis infection hospitalizations; 15, 025 organ dysfunction matched all-cause nonsepsis hospitalizations; and all with live discharge. Measurements and Main Results: Among 18, 210 pediatric severe sepsis hospitalizations, 1, 024 (5.6%) underwent device placement. Specifically, 3.5% had new gastrostomy, 3.1% new tracheostomy, 0.6% new vascular access devices, 0.4% new ostomy procedures, and 0.1% amputations. One-hundred forty hospitalizations (0.8%) included two or more new devices. After applying the Nationwide Readmissions Database sampling weights, there were 55, 624 pediatric severe sepsis hospitalizations and 1, 585, 194 all-cause nonsepsis hospitalizations with live discharge in 2016. Compared to all-cause pediatric hospitalizations, severe sepsis hospitalizations were eight-fold more likely to involve new device acquisition (6.4% vs 0.8%; p < 0.001). New device acquisition was also higher in severe sepsis hospitalizations compared with matched nonsepsis infection hospitalizations (5.1% vs 1.2%; p < 0.01) and matched all-cause hospitalizations with similar organ dysfunction (4.7% vs 2.8%; p < 0.001). Conclusions: In this nationwide, all-payer cohort of U.S. pediatric severe sepsis hospitalizations, one in 20 children surviving severe sepsis experienced new device acquisition. The procedure rate was nearly eight-fold higher than all-cause, nonsepsis pediatric hospitalizations, and four-fold higher than matched nonsepsis infection hospitalizations. Abstract : Supplemental Digital Content is available in the text.